2018
DOI: 10.1093/pm/pny096
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Patient Expectations of Postoperative Pain Are Associated with Moderate to Severe Acute Pain After VATS

Abstract: None of the preoperative psychosocial measures were associated with the moderate to severe acute pain after VATS. Average expected postoperative pain was the only measure associated with the development of moderate to severe acute pain after VATS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 44 publications
3
34
1
3
Order By: Relevance
“…In this retrospective study of 1164 adult patients undergoing VATS, the prevalence of moderate-severe postoperative pain over 48 hours was 15.7%. This finding differs from the results obtained by Emine et al 6 , who reported a higher incidence of pain (59%). This is mainly owing to different patient characteristics, diverse types of surgery performed and distinct follow-up periods.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this retrospective study of 1164 adult patients undergoing VATS, the prevalence of moderate-severe postoperative pain over 48 hours was 15.7%. This finding differs from the results obtained by Emine et al 6 , who reported a higher incidence of pain (59%). This is mainly owing to different patient characteristics, diverse types of surgery performed and distinct follow-up periods.…”
Section: Discussioncontrasting
confidence: 99%
“…Younger age is another consistent risk factor for moderate-severe pain following VATS, similar to a study including robotic-assisted thoracic surgery, VATS and open lobectomy 5 , but in contrast to a recent study reporting no age-related differences by limited sample size 6 . This finding could be explained by the fact that the old had higher pain threshold, more peripheral neuropathy and less scar with less stiffness, contributing to less pain.…”
Section: Discussionsupporting
confidence: 65%
“…This result was consistent with previous reports. [3,33] Considering some patients were unwilling to take any extra analgesic drug even though they were unsatisfactory to the analgesia effect or their 9 sleep was disturbed by pain, we defined postoperative inadequate analgesia as not only patients with moderate to severe pain and required extra analgesic drug, but also patients with bad sleep quality and low satisfaction. This definition comprehensively comprises the real patients with inadequate analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…[29] The criteria for inclusion in the study were age from 18 to 70, ASA classification Ⅰ to Ⅲ, and voluntarily received patient-controlled intravenous (PCIA) treatment. The exclusion criteria included the following: (1) history of mental illness, chronic pain, and alcohol or drug abuse; (2) remarkably abnormal liver and/or kidney function (more than two times of the normal); (3) allergy to related opioid drugs; (4) women during pregnancy or lactation.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation